2021
DOI: 10.1038/s41598-021-93881-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of liver biopsies before and after direct-acting antiviral therapy for hepatitis C and correlation with clinical outcome

Abstract: Direct-acting antivirals (DAA) have replaced interferon (IFN)-based therapies for hepatitis C virus. In this retrospective clinical study, we examined differences in histopathologic features in paired liver biopsies collected from the same patient before and after DAA and correlated these findings with clinical outcome. Biopsies (n = 19) were evaluated by quantitative imaging analysis to measure steatosis and fibrosis. Most patients had decreased steatosis in their post-treatment, follow-up biopsies. However, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 60 publications
2
4
0
Order By: Relevance
“…As expected, in our study, higher values of AST, ALT, and ALP were associated with more advanced fibrosis stages before and after DAA treatment. These results agree with other studies that report a normalization of these biomarkers after HCV elimination [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…As expected, in our study, higher values of AST, ALT, and ALP were associated with more advanced fibrosis stages before and after DAA treatment. These results agree with other studies that report a normalization of these biomarkers after HCV elimination [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the HCVinfected patients with superimposed conditions such as metabolic syndrome and obesity should be evaluated for liver steatosis after SVR [26]. In several studies, the hepatic steatosis in HCV patients before SVR was assessed by liver biopsy, and 40-80% of cases had liver steatosis [27,28]. In our study, the prevalence of liver steatosis in patients who achieved SVR with DAAs was 66,42%, independent of the type of regimen used.…”
Section: Discussionmentioning
confidence: 53%
“…The majority of studies (21 out of 30) did not show a significant change in mean BMI or weight after SVR. Conversely, 7 studies revealed an increase in BMI after SVR, 27,40,90,114–117 while 3 studies showed a reduction in mean BMI 53,81,118 …”
Section: Resultsmentioning
confidence: 99%